Online And Offline Learning ComparisonIn The New Normal Era - Valentino, V.H.; Satria Setiawan, Heri; Tri Habibie, Muhammad; Ningsih, Retna; Katrina, Dona; Syah Putra, Arman (CV. Inara, 2021)
There are many learning media during the Covid 19 pandemic, some use online media and offline media, online media are also of many kinds, some are in the form of videos, pictures or writing, but there are also many learning media that combine all learning media, examples are online media youtube, with youtube media students will be able to view learning material repeatedly because videos can be downloaded. The method used in research is to use the literature review method, a method that can help in this study because it can find new problems in future research. The problem raised in this research is wanting to know the right media and making comparisons of online and offline media during the new normal period after the COVID-19 pandemic. This research produces data that can prove that the right media is in the new normal period, this is done to common interests and the nation.